2013
DOI: 10.1103/physrevb.87.125421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the image charge effect on excitonic energy structure in organic-inorganic multiple quantum well crystals

Abstract: We have experimentally compared the excitonic properties of hybrid multiple quantum wells, (C 6 H 5 -C 2 H 4 NH 3 ) 2 PbBr 4 and (C 4 H 9 NH 3 ) 2 PbBr 4 , using photoluminescence, reflection, and photoluminescence excitation measurements. We focused on the contribution of the image charge effect (ICE) to the excitonic energy structure in these materials which have different dielectric constants of the barrier layers. We have found that the binding energies of the 2s and 3s excitons are considerably enhanced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 25 publications
6
83
0
Order By: Relevance
“…712 Here, the low dielectric constant of the adjacent organic layers provides poor shielding of the electrons and holes in the inorganic layers leading to the exciton's dielectric confinement. The E b values for n = 1 perovskites are typically above 300 meV, 13 comparable to those of certain organic molecules. 14 These tightly bound excitons in 2D perovskites have enabled varied applications in luminescence.…”
Section: Introductionmentioning
confidence: 90%
“…712 Here, the low dielectric constant of the adjacent organic layers provides poor shielding of the electrons and holes in the inorganic layers leading to the exciton's dielectric confinement. The E b values for n = 1 perovskites are typically above 300 meV, 13 comparable to those of certain organic molecules. 14 These tightly bound excitons in 2D perovskites have enabled varied applications in luminescence.…”
Section: Introductionmentioning
confidence: 90%
“…Electronic coupling between inorganic layers is negligible because of the high energy barriers formed by the PEA layers. This 2D material naturally forms repeating quantum well structures, as schematically shown in Figure 1B, that tightly confine excitons within the inorganic layers, leading to high exciton binding energies (350 -480 meV) 37 and strong, stable PL at room temperature. 36 Narrow, violet PL was previously reported for (PEA)2PbBr4.…”
mentioning
confidence: 99%
“…Therefore, we can estimate ¦ LT at 4 K to be 7 meV. It is reported that ¦ LT and the exciton binding energy of the two-dimensional perovskite lead bromide material (C 4 H 9 NH 3 ) 2 PbBr 4 are about 70 meV and 390 480 meV, 22,23 respectively. Considering the relation among ¦ LT , the oscillator strength, and the exciton binding energy, 24,25 we can roughly estimate the exciton binding energy of CH 3 NH 3 -PbBr 3 at low temperature to be 80100 meV, which is almost in accordance with the reported value of 76 meV.…”
mentioning
confidence: 99%